ANALYSIS OF SERVICE QUALITY AND BRAND IMAGE ON CUSTOMER SATISFACTION THROUGH PURCHASE DECISIONS AS INTERVENING VARIABLE (CASE STUDY E-COMMERCE SHOPEE AT VILLA GALAXY HOUSING RT 002) - Vierdwiyani, Deviana; Afriapollo Syafarudin (Dinasti Publisher, 2020)
This study aims to determine the effect of service quality and brand image on purchasing decisions and customer satisfaction in Shopee. This study also examines the indirect effect of service quality and brand image on customer satisfaction with purchasing decisions as a mediating or intervening variable. The study was conducted at RT 002 Villa Galaxy. The sample in this study was Shopee customers with a purposive sampling method. The number of respondents who participated in this study were 100 respondents. Data collection was carried out through a questionnaire with a Likert scale of 1-5. The method and analysis tool is Partial Least Square (PLS) with Smart PLS Software 3. The results of the study show that service quality has a significant positive effect on purchasing decisions, brand image has a significant positive effect on purchasing decisions, service quality has a significant positive effect on customer satisfaction, brand image significant positive effect on customer satisfaction, purchasing decisions significantly positive effect on customer satisfaction, and purchasing decisions mediate the effect of service quality and brand image on customer satisfaction. Shopee can improve service quality and brand image so that purchasing decisions and customer satisfaction can be improved, through improved features and application services.